2018
DOI: 10.18683/germs.2018.1139
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of Mycoplasma pneumoniae among patients with atypical pneumonia in Tehran, Iran

Abstract: Introduction Mycoplasma pneumoniae is a major cause of atypical community-acquired pneumonia) CAP) with a prevalence range of 15-20% and up to 40% in adults and children, respectively. In Iran, the recorded frequency ranges between 1-6.15%. We aimed to investigate the frequency of M. pneumoniae among patients with atypical pneumonia acquired from the community. Methods Over a period of 5 months between January and June 2017, 520 patients with suspected CAP, who had been to the hospital outpatient clinics of Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The first one was conducted by Arfaatabar et al. [ 27 ], who reported a high frequency (26.4%) of this agent in their studied population. The second one was done by our own group and found the rate of M. pneumoniae to be 25.2% [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first one was conducted by Arfaatabar et al. [ 27 ], who reported a high frequency (26.4%) of this agent in their studied population. The second one was done by our own group and found the rate of M. pneumoniae to be 25.2% [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…MPP is one of the most common forms of CAP in children . Increasing evidence has shown that PD has antioxidative and anti‐inflammatory effects .…”
Section: Resultsmentioning
confidence: 99%
“…MPP is one of the most common forms of CAP in children. 2,17 Increasing evidence has shown that PD has antioxidative and anti-inflammatory effects. 18,19 So, in this study, the effects of PD ( Figure 1A) against MPP were investigated both in vivo and in vitro.…”
Section: Mp-induced Lung Injury In Mice By Inhibiting the Expression mentioning
confidence: 99%
“…42 In a 5-month study (from January 2017 to June 2017), Arfaatabar et al observed a high frequency of M. pneumoniae among 520 patients with CAP in Tehran, Iran. 43 Su et al determined that M. pneumoniae was highly prevalent in hospitalized children with community-acquired M. pneumoniae pneumonia (MPP) (66.4% [221/333 pediatric patients]). 44 A retrospective study by Cheng et al investigated the epidemiology of M. pneumoniae in Chinese children with respiratory infections from June 2016 to May 2021.…”
Section: Discussionmentioning
confidence: 99%